Evaluation of the utility of cardiac biomarkers for risk stratification in patients with lower extremity artery disease: A retrospective study - Leyla Schweiger; Reinhard B. Raggam; Gabor Toth-Gayor; Philipp Jud; Alexander Avian; Viktoria Nemecz; Katharina Gütl; Marianne Brodmann; Thomas Gary (PLoS ONE, 2025)
Critical limb threatening ischemia (CLTI) is associated with a one-year mortality rate of up to 25% making prompt diagnosis essentially. This study aims to investigate if cardiac biomarkers may serve as an effective tool for risk stratification in patients with lower extremity artery disease (LEAD). For this cross-sectional retrospective analysis, 21712 patients with LEAD were screened for eligibility from 2004 to 2020. Out of these patients, 367 were included and subdivided into those with CLTI and those without CLTI. Cardiac biomarkers, including N-terminal prohormone of brain natriuretic peptide (NT-proBNP), troponin, NT-proBNP/troponin ratio, creatin kinase myocardial band (CK-MB) and myoglobin, were retrospectively analyzed. Fifty-nine patients had CLTI (16.1%) with higher rates of NT-proBNP, NT-proBNP/troponin ratio, CK-MB and myoglobin (all p < 0.05) compared to non-CLTI patients. In univariate analysis, NT-proBNP, NT-proBNP/troponin ratio, CK-MB, myoglobin, age, C-reactive protein and non-insulin dependent diabetes mellitus (NIDDM) were associated with CLTI (all p < 0.05). In multivariate analysis, age and NIDDM remained significant predictors (all p < 0.05) while cardiac biomarkers were not independently associated with CLTI. Troponin, NT-proBNP and myoglobin were associated with mortality in univariate analysis (all p < 0.05). In multivariate analysis, troponin only remains to be associated with mortality (p = 0.001). Selected cardiac biomarkers failed to demonstrate statistically significant differentiation between CLTI and non-CLTI patients with LEAD, while troponin may be potentially associated with mortality.